Comparative evaluation of autosomal STRs and X-chromosome STRs as a complement of autosomal STRs in kinship testing in Southern Han Chinese - Yinming Zhang; Zhengliang Yu; Xiaoting Mo; Xingchun Zhao; Wanshui Li; Hong Liu; Chao Liu; Riga Wu; Hongyu Sun (Taylor & Francis Group, 2021)
Nowadays, kinship testing is very common in forensic caseworks, but the power of autosomal short tandem repeats (A-STRs) may be limited in complex cases. X-Chromosome short tandem repeats (X-STRs), having a unique heritage mode, should be of special use in some deficient cases. To evaluate and compare the potential of A-STR and X-STR as supplement genetic markers in deficient kinship testing, we simulated 10,000 duos for each of 18 kinds of relationships involving full sibling, half-sibling, grandparent-grandchild, and uncle/aunt-nephew/niece. Loci from STRTyper10, PowerPlex 16, and Investigator Argus X-12 were studied in Southern Han Chinese and the distribution of likelihood ratio (LR) values was analysed. With the addition of the X-12 system, the distribution of LR values for the full sisters, paternal half-sisters, paternal grandmother-granddaughters, maternal aunt-nieces, and maternal aunt-nephews separated much more obviously from those of unrelated duos, and the effectiveness was 1.0000, 0.99865, 0.9991, 0.8996 and 0.9634, respectively, which was more efficient than A-STRs. For the individual duos with other relationships, the effects of adding X-STRs and A-STRs were similar. Therefore, for the Southern Han Chinese, X-STRs can be very useful in kinship testing involving full sisters, paternal half-sisters, paternal grandmother-granddaughters, and maternal aunt-nieces/nephews.